2013
DOI: 10.1111/vox.12033
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive methods for haemoglobin screening in prospective blood donors

Abstract: Background and ObjectivesThe haemoglobin level of prospective blood donors is usually performed on blood obtained by from the finger pulp by fingerstick with a lancet and filling a capillary tube with a sample. New noninvasive methods are now available for rapid, noninvasive predonation haemoglobin screening. Materials and MethodsProspective blood donors at our blood centre were tested, in two different trials, as follows: by the NBM 200 (OrSense) test (n = 445 donors) and by the Pronto-7 (Masimo) test (n = 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 17 publications
4
61
1
Order By: Relevance
“…Belardinelli et al (2013) found that the Pronto-7 had a similar bias of -0.53 g/dL, SDD of 1.04 and 95% limits of agreement from -2.57 to 1.51 when compared to the Beckman Coulter Cell Counter at sea level. That study also showed the same trend bias that we observed in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Belardinelli et al (2013) found that the Pronto-7 had a similar bias of -0.53 g/dL, SDD of 1.04 and 95% limits of agreement from -2.57 to 1.51 when compared to the Beckman Coulter Cell Counter at sea level. That study also showed the same trend bias that we observed in our study.…”
Section: Discussionmentioning
confidence: 95%
“…An important issue in the measurement of capillary hemoglobin seems to be the pre-analytical variability of sampling related not only to anatomical differences at finger pulp circulation but also difference between venous and capillary blood has to be taken into account. 18) Although NBM 200 had the highest specificity, having a very low sensitivity, more than 80% of donors who did not satisfy the Hb criteria would have been accepted for blood donation (Table 3) Hb measurement remains a conflictive issue in routine donor acceptance procedures and these devices needs to be improved prior to apply in the blood…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al [35] evaluated the usefulness of the NBM-200 for blood donor screening and concluded that wrong decisions could occur when deciding eligibility for blood donation using this device. Another reports of blood donor screening using the NBM-200 are available [36,37]. Pinto et al compared performance of fingerstick sampling and NBM-200, and significantly lower level of percentage error was found in NBM-200 compared to reference value (tHb).…”
Section: Other Situationsmentioning
confidence: 99%